Teaching foreigner languages in higher education: Challenges in times of the pandemic - Alves, D. R.; Belchior-Rocha, H.; Casquilho-Martins, I. (EDULEARN22 Proceedings, 2022)
Knowledge and proficiency in more than one language are fundamental skills in a globalized world. In higher education, foreign language learning has proven to be an important tool for academic success and for integration in the labor market. In this sense, the aim of this study was to analyze the adaptation of teaching/learning foreign languages in online and hybrid models in a public university during the pandemic and of the utilized resources and strategies. We used a focus group technique with the language teachers to identify the main challenges and the results obtained between 2019 and 2021. We complemented this analysis with students' evaluation of language teaching in the same period. The results show the pandemic caused difficulties in teaching and that the adaptation to the online and hybrid models forced the creation of new pedagogical strategies, mainly due to the requirements of language teaching and specific teaching-learning methodologies. After the pandemic and with proper preparation and support, new pedagogical practices will utilize some adaptations incorporating digital technologies. Thus, a hybrid approach represents a real trend and possibility for language teaching in the post-pandemic context. The collected data from the students´ evaluation showed a very positive assessment and despite the difficulties, they point to the teacher's interest in making the students learn, as well as keeping them motivated to do so, reinforcing the relevance of these curricular units in their learning and professional growth.